Ending institutions: Rule enforcement in self-governance systems - Pedro, Antonio C. (Animo Repository, 2018)
How are rules enforced in the absence of an organization with coercive powers? I examine the role of informal institutions in supporting self-enforcement of rules through ethnographic research on a popular form of community-based gambling in the Philippines. In ending, a reputation-based mechanism shapes exchange relations between bettors and bet-takers, and among members of a local community. Social norms about sharing one’s winnings (balato) provide community members with an interest in the outcome of these exchange relations, thereby strengthening the ability of bettors to acquire information about the reputation of various bet-takers. In consequence, bet-takers exert efforts to safeguard their reputation, and comply with informal rules about the immediate and complete delivery of winnings. The findings suggest that when communities are small enough so that members are able to observe each other, but not too small so that no individual possesses all the relevant information, then social norms that generate effective transmission of reputational information provide sufficient institutional support for self-governance. © 2017, © The Author(s) 2017.